Rapid evolution of female-biased genes among four species of Anopheles malaria mosquitoes - Papa, Francesco; Windbichler, Nikolai; Waterhouse, Robert M.; Cagnetti, Alessia; D'Amato, Rocco; Persampieri, Tania; Lawniczak, Mara K.N.; Nolan, Tony; Papathanos, Philippos Aris (Genome Research, 2017)
Understanding how phenotypic differences between males and females arise from the sex-biased expression of nearly identical genomes can reveal important insights into the biology and evolution of a species. Among Anopheles mosquito species, these phenotypic differences include vectorial capacity, as it is only females that blood feed and thus transmit human malaria. Here, we use RNA-seq data from multiple tissues of four vector species spanning the Anopheles phylogeny to explore the genomic and evolutionary properties of sex-biased genes. We find that, in these mosquitoes, in contrast to what has been found in many other organisms, female-biased genes are more rapidly evolving in sequence, expression, and genic turnover than male-biased genes. Our results suggest that this atypical pattern may be due to the combination of sex-specific life history challenges encountered by females, such as blood feeding. Furthermore, female propensity to mate only once in nature in male swarms likely diminishes sexual selection of post-reproductive traits related to sperm competition among males. We also develop a comparative framework to systematically explore tissue- and sex-specific splicing to document its conservation throughout the genus and identify a set of candidate genes for future functional analyses of sex-specific isoform usage. Finally, our data reveal that the deficit of male-biased genes on the X Chromosomes in Anopheles is a conserved feature in this genus and can be directly attributed to chromosome-wide transcriptional regulation that de-masculinizes the X in male reproductive tissues.